Financial Inclusion: An initiative towards women empowerment against social norms - Shalu Kumari (International Ecsis Association, 2022)
Despite general progress made in terms of Financial Inclusion worldwide, the gender gap has remained unaltered since 2011. The study aims to identify the impact of Financial Inclusion on women's empowerment. This research used descriptive qualitative methods. Content analysis approaches are used to analyze secondary data. Various reports published by the Reserve Bank of India (RBI) and other financial institutions have been used as relevant input. Besides, research articles from different reputed journals, websites, and magazines have been used. The study found that some strategies have been implemented to minimize the gender gap in access to financial services. The systems are Know Your Customer (KYC) norms, no-frill accounts; an extension of the financial services and became medium of empowering women; the introduction of a small loan to make the females capable and self-dependent. The paper provides implications about strategies to overcome the barriers women face to access and use financial services in the condition of social norms constraining women's capacity to access and meaningfully use financial services.